Analysis The Level of Compliance of Hospital Human Resources in Writing The Status of Inpatient Medical Record Dr Sayidiman Hospital and The Influences Factors - Ratnawati Ratnawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The quality of medical records in hospitals also determines the quality of service, completeness of writing Medical Records documents correctly and correctly is very important. The purpose of this study was to analyze the level of compliance of hospital human resources in writing the status of the inpatient Medical Record Dr. Sayidiman Magetan Regional Hospital and the factors that influence it. The design of this study was an observational quantitative study with a cross section approach with the focus of the research directed to be analyzing the level of compliance of hospital human resources in writing the status of the inpatient Medical Record Dr Sayidiman Magetan Regional Hospital and the factors that influenced it with a sample of 192 respondents taken with the Simple Random Sampling technique. The findings found that most of the respondents have high motivation that is 144 respondents (75%). Most of the respondents care to write in the medical record that is 160 respondents (83.3%). Most of the respondents have a high appreciation of 136 respondents (70.8%). Most of the respondents did not comply doing medical record writing of 107 respondents (55.7%). Based on the Linear Regression analysis the motivation variable on compliance p-value 0.015 <0.05, the variable concern for compliance p-value 0.025 <0.05 then H0 is rejected so there is the influence of motivation and concern for compliance with medical record writing by health professionals in Regional General Hospital Dr. Sayidiman Magetan. Linear regression variable rewards for compliance shows that the p-value of 0.665> 0.05 then H0 is accepted so it is concluded that there is no effect of rewards on compliance with writing medical records by health professionals at the Dr Sayidiman Magetan Regional General Hospital. It is expected that respondents can comply to fill out medical records so that the delivery of care to passion can be well integrated